IN VITRO EVALUATION OF HYPOLIPIDEMIC EFFECT OF EXTRACTS OF MEDICINAL DRACAENA CINNABARI BALF. F. RESIN: In vitro evaluation of hypolipidemic effect - YASSER HUSSEIN EISSA MOHAMMED; DEEPIKA HS; FARES HEZAM AL-OSTOOT; ZABIULLA; ANILAKUMAR; SHAUKATH ARA KHANUM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to in vitro evaluate of hypolipidemic effect of extracts of medicinal Dracaena cinnabari Balf. f. resin. Methods: About 800 g of dry powder of the resin of dracaena cinnabar was taken in a Soxhlet apparatus and subjected for sequential extraction of solvents from non-polar to polar end (hexane, benzene, diethyl ether, dichloromethane, chloroform, ethyl acetate, acetone, ethanol, methanol, and water); the extract samples were kept at 4°C for further assays. All the extracts were subjected to glucose uptake assay. Results: The ethanol extract showed significant (p<0.05) hypolipidemic effect by decreasing the activity of enzyme such as significant reduction in the pancreatic lipase enzyme, malic dehydrogenase enzyme, and glucose-6-phosphate dehydrogenase enzyme with IC50~13, ~13, and ~14, respectively. This results were similar to the standard drug atorvastatin with IC50~12, ~16, and ~17, respectively. Ethanol extract exhibited significant atherogenic index and percentage protection against hyperlipidemia. The potential biological activity of ethanol extract may be attributed to the highest polarity which needs further investigation.